Editorial for the special issue "spatial and regional aspects of health" - Anna-Theresa Renner; Rita Santos; Benedetta Pongiglione; Roman Hoffmann (REGION, 2022)
The health crisis caused by the COVID-19 pandemic highlights, more than ever, the necessity of scientific research to inform policy action. During such a crisis it is vital that any measure taken by policy makers mitigates the consequences on health without causing long-lasting social and economic harm. Spatial aspects play an important role here: knowledge about the spread of a disease through space and social networks, the effectiveness of different policy responses, and the economic and social implications for the population are of particular relevance. As any policy action is embedded in its institutional and social environment, not every measure is effective in all contexts. Moreover, infectious diseases can spread at different speed in different places, requiring tailored interventions. Careful evaluation and comparison of different settings, including the organization of the healthcare systems and the geographic and demographic characteristics of a region or country, are therefore essential. The COVID-19 pandemic has made manifest the importance of the spatial and geographical dimension of health, however, the relevance of this interlinkage is not limited to the spread of contagious diseases. Differences in accessibility of services between urban and rural regions, the varying costs of access to healthcare for different (socioeconomic) groups of the population, the impact of these on healthcare utilization, and environmental shocks on population health are just a few examples illustrating the close link between space, socioeconomic factors and health. This special issue of REGION is presented in two parts. In the first part, papers explore the spread and impact of the COVID-19 pandemic on the health and economy. In the second part, papers investigate regional and spatial aspects of the healthcare sector with a focus on health disparities.
Keywords: 330